Protecting the rights of Filipina Migrant Workers: An analysis of bilateral labour agreements between the Philippines and Canada - Le Nguyen, Rosaleen (Université d'Ottawa | University of Ottawa, 2023)
The Philippines is one of the largest labour sending countries in the world, sending a large number of migrant workers abroad every year, including Canada. As such, the Philippines has created and implemented labour export policies to address the protection of its workers’ rights abroad. One of the tools the Philippines utilizes to ensure this are bilateral agreements with a select number of receiving countries. This paper will examine how pursuant Canadian bilateral agreements are with respect to Filipina migrant workers rights as established in the The Migrant Workers and Overseas Act. This will be achieved through the analysis of bilateral labour agreements between the Philippines and Canada in reflection of the Philippines’ labour migration export policies, namely the Migrant and Overseas Workers Act. By conducting a policy analysis of the Memorandum of Understandings (MOU) between the Philippines and Manitoba, British Columbia, Saskatchewan, Alberta, and Yukon, this paper highlights the lack of enforcement of the protection of Filipino migrant workers’ rights and gender sensitive elements in the agreements, important elements of the Migrant and Overseas Workers Act. The reality of Filipina workers’ rights in Canada are discussed despite the existence of these MOUs. Keywords: The Philippines, TFWP, labour migration, immigration, gendered migrant rights, bilateral labour agreements, labour export policies.